X-ray computed microtomography for the structural analysis of jewelry from the Museum "Royal Tombs of Sipán". (December 2020) - de Azeredo, Soraia Rodrigues; Cesareo, Roberto; Dominguez, Angel Guillermo Bustamante; Lopes, Ricardo Tadeu
Abstract : Precious ornaments from the Museum Royal Tombs of Sipán were analyzed by X-ray computed microtomography (microCT). The ornaments analyzed were golden earrings produced by the Moche culture that flourished along the north coast of present-day Peru between approximately 100 and 600 AD. Sipán, also known as Huava Rajada, is a mochica archaeological complex in the north of Peru. In particular, the spectacular jewelry, mainly composed of gold, silver, and copper alloys, gilded copper, and tumbaga, from the Museum "Royal Tombs of Sipán, " in Lambayeque, north of Peru, are some of the most sophisticated metalworking ever produced of pre-Columbian America. A portable microCT system consisting of a high-resolution flat panel detector and a mini X-ray tube were used for the structural analysis of these ornaments. The microCT images show parts of the internal structure, highlighting the manufacturing technique and gold sheets joining techniques of the Moche artisans. Furthermore, the advantage of using the portable microCT system for nondestructive testing is clear when the sample cannot be taken to the laboratory.